The Influence of Commuter Marriage on Marital Satisfaction among Couples in Public Universities in Enugu State, Nigeria - Mgbemena Rachael; Ezeda Patricia Kalu (International Journal of Home Economics, Hospitality and Allied Research)
This study investigated the influence of commuter marriage on marital satisfaction among academic staff in public universities in Enugu State, Nigeria. Specifically, it aimed to explore the underlying motivations for commuter marriage, identify challenges faced by couples in such arrangements, and propose strategies to improve marital satisfaction. A descriptive survey design was adopted, and the study was conducted across two public universities: the University of Nigeria, Nsukka (UNN), and Enugu State University of Science and Technology (ESUT). Due to the absence of institutional records identifying commuter marriage couples, a purposive sampling technique was used to select 124 participants 64 from UNN and 60 from ESUT across various faculties and departments. Data were collected using a structured questionnaire, which was face-validated by three experts in related fields. Data analysis involved the use of mean and standard deviation to summarize responses. The results revealed several key reasons for engaging in commuter marriage, including career demands and geographic constraints. Participants also reported a range of emotional, social, and logistical challenges affecting their marital satisfaction. In response, the study identified practical strategies to enhance relationship quality, including institutional support systems, improved communication, and professional counselling services. The findings suggest that while commuter marriage may be a necessary choice for many academic couples, it introduces significant stressors that can undermine marital harmony. The study concludes with a recommendation for the provision of targeted marital counselling services within university systems to support affected staff members and promote overall well-being.